(untitled) (American Journal of Public Diplomacy and International Studies (2993-2157), 2023)
In accordance with the Constitution of Georgia, the right of opinion and its free expression are protected. /Constitution of Georgia, article 17/. It also establishes the prerequisites for limiting the right: “Restriction of these rights is permitted only in accordance with the law, to ensure the necessary state or public security or territorial integrity in a democratic society, to protect the rights of others, to prevent the disclosure of confidential information, or to ensure the independence and impartiality of the judiciary.” The judge has the greatest responsibility in the administration of justice. At any moment, whether it is the performance of official duties or the implementation of other activities, he bears the greatest responsibility. The judge, together with his professional and personal qualities, is an important basis for society’s trust in the court and strengthening the judiciary. That is why any of his behavior and actions, publicly expressed opinion or statement directly affects the image and reputation of a judge, since society also generalizes the impression received when observing one particular judge to the entire system.